(untitled) (Italian Journal of Public Health, 2009)
Background: Obesity is actually a discernible issue in prosperous western society and is dramatically increasing in children and adolescents. Many studies indicate that obesity in childhood may become chronic disease in adulthood and, particularly, those who are severely overweight have an increased risk of death by cardiovascular disease. Understanding the determinants of life style and behavior in a person’s youth and making attempts to change children’s habits is considered a key strategy in the primary prevention of obesity. This study aims to find a correlation between Body Mass Index, (BMI), physical activity and eating behavior and to identify, eventually, risks, protective factors and possible directions for interventions on incorrect nutritional/physical activity and intra-familiar life styles in a sample of young adolescents in a small town of Western Sicily. Methods: The research surveyed the entire population of the last three curricular years of two Primary Schools in a town of western Sicily, (n=294). The instrument used for the survey was a questionnaire containing 20 different items with multiple choices answers. Personal information, physical activity and eating behaviors were collected both for parents and students to cross students’ and parents’ characteristics. Data were codified and statistical analysis was computed through Statistica and Openstat software. Results: Data obtained demonstrated a relevant percentage (18%) of obese children. Prevalence of overweight was high as well, (23%), and many in this area (12%) were at risk since they were on the limits of the lower class. A significant association was found between the percentage of students classified as having an elevated BMI and a sedentary habit and/or an incorrect eating behavior. Among the overweight and obese children a direct statistical association was also shown between the weight of their parents and some daily life styles. An inverse association, on the contrary, was observed between those variables and the cultural level of the family. Cultural level, in fact, was significantly associated with having breakfast, fruit and vegetable consumption and practice of physical exercise. Multi linear regression analysis showed the weight of some independent variables which were more strictly correlated with children’s BMI. Conclusions: Increasing the proportion of adolescents meeting recommended dietary and physical activity guidelines has been identified as an important strategy to contrast the epidemic increase in obesity, especially in western countries. This study stressed the need to increase the knowledge and monitoring of the consequent behaviors of adolescents with regards to dietary habits and the practice of physical activity. School, communities and families are considered the best pathways to disseminate correct information and knowledge and the more suitable channels to raise the awareness of the importance of correct dieting and regular physical activity School and community-based intervention programs are, then, strongly requested to activate preventive actions early in life and mainly in the development age. The importance of the family andof the social context factors in health behavior was also emphasized. A familiar eco-systemic model that takes into account the whole bio-social-psychological aspects was also sustained for a global therapeutic approach to the obese child.